A transformerless three‐level three‐phase boost PWM inverter for PV applications. Issue 10 (16th July 2021) - Palanisamy, Aswin; Siwakoti, Yam P.; Mahajan, Akshay; Long, Teng; Kashani, Omid Forati; Blaabjerg, Frede
Abstract: Multilevel converters have seen rising demands in the past decades, due to their increased power ratings, enhanced power quality, low switching losses and reduced electromagnetic interference. Prominent among them are the three‐level (3L) neutral point clamped and the flying capacitor inverter topologies along with their derivatives. Nevertheless, the main drawback of these topologies is the requirement of a front‐end boost DC–DC converter to compensate the high dc‐link voltage demand, which is usually twice the grid peak voltage. This multi‐stage power conversion further pulls down the overall system efficiency. A single‐stage dc–ac power converter with boost capability offer an interesting alternative compared to the two stage approach. Considering this aspect, a novel three‐level three‐phase boost type inverter is introduced in this paper for general‐purpose applications (prominently grid‐connected renewable energy). The proposed inverter would reduce the DC‐link voltage requirement to half using the same or even less number of active and passive components, compared to the conventional three‐level neutral point clamped and flying capacitor family. The principle of operation and theoretical analysis are discussed in detail. The design methodology along with simulation and experimental waveforms for a 5 kVA inverter are presented to prove the concept of the proposed inverter topology for practical applications.